Operating Variables on Production of High Purity Bio-silica from Rice Hull Ash by Extraction Process - Soen Steven; Elvi Restiawaty; Yazid Bindar (Institute for Research and Community Services, Institut Teknologi Bandung, 2022)
The huge amount of rice hull biomass available in Indonesia can be utilized as raw material for bio-silica production. This study investigated the production of high-purity bio-silica from rice hull ash through an alkaline extraction process. A full factorial design (FFD) was used to screen for significant effects of the observed variables. Three operating variables – acid concentration, solvent to feed ratio (RS/F), and extraction time – were investigated with the purpose of obtaining a high yield and high purity of bio-silica. Yield and purity above 96% were achieved by using pretreatment with 1 mol/L HCl. Employing an RS/F of 5 and a longer extraction time improved the bio-silica yield. The operating variable that enhanced the bio-silica yield and purity most was acid concentration. All variable interactions had an insignificant effect on purity, while two interacting variables had a significant effect on bio-silica yield. Based on the results of this study, rice crop residue can be optimally converted to a bio-silica product in terms of yield and purity by optimizing the most effective operating variables.